Zhejiang Semir Garment Co., Ltd. - McFarlan, F. Warren (Franklin Warren); Jiao, Jie; Fang, Yuren ([London] : SAGE, 2016)
Board chairman of Zhejiang Semir Garment Co. Qiu Guanghe attributes much of its success to its business model. Adopting the virtual production model, Semir Garment controls product design and brand building, but outsources production and logistics characterized by huge investment but relatively small profits to other companies. Its sales are done through chain stores and franchised outlets. This book evaluates the Zhejiang Semir Garment Co. model.
Originally Published in: McFarlan, F. W., Jiao, J., & Fang, Y. (2012). Zhejiang Semir Garment Co., Ltd. 0-912-331. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Zhejiang Semir Garment Company; Clothing trade -- China -- Case studies; Business planning -- Case studies